2010
DOI: 10.1002/jnr.22382
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of spontaneous Ca2+ spikes by metabotropic glutamate receptors in primary cultures of rat cortical neurons

Abstract: Periodic and spontaneous Ca 21 spikes are observed in neurons during development of the central nervous system, and spontaneous changes in intracellular Ca 21 concentration in neurons play important roles in the development of neural circuits. To clarify the roles of metabotropic glutamate receptors (mGluRs) in the regulation of spontaneous Ca 21 spikes, we investigated the effects of selective and nonselective mGluRs ligands on primary cultures of rat cortical neurons. Cultured cortical neurons expressed all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…This finding is consistent with previous reports that have demonstrated Glu receptor signaling pathways regulate SCO behavior (Dravid and Murray, 2004;Koga et al, 2010). We also show that both competitive and noncompetitive N-methyl-D-aspartate receptor antagonists (AP5 and MK-801) suppress both basal and bifenthrinaugmented SCO activity.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous reports that have demonstrated Glu receptor signaling pathways regulate SCO behavior (Dravid and Murray, 2004;Koga et al, 2010). We also show that both competitive and noncompetitive N-methyl-D-aspartate receptor antagonists (AP5 and MK-801) suppress both basal and bifenthrinaugmented SCO activity.…”
Section: Discussionsupporting
confidence: 93%
“…SCOs in cultured neuronal networks are dependent on action potentials and the release of synaptic neurotransmitter vesicles (Dravid and Murray, 2004). A number of studies have suggested that SCO activity is highly dependent on the balance of ongoing excitatory ionotropic glutamatergic and inhibitory GABAergic neurotransmission within the neuronal network (Dravid and Murray, 2004;George et al, 2009, Koga et al, 2010Pacico and Mingorance-Le Meur, 2014). In addition to ionotropic Glu receptors, both type I and type II metabotropic Glu receptors also modulate SCO patterns (Dravid and Murray, 2004;Koga et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that SCO activity is highly dependent on the balance of ongoing excitatory ionotropic glutamatergic and inhibitory GABAergic neurotransmission within the neuronal network (Dravid and Murray, 2004;George et al, 2009, Koga et al, 2010Pacico and Mingorance-Le Meur, 2014). In addition to ionotropic Glu receptors, both type I and type II metabotropic Glu receptors also modulate SCO patterns (Dravid and Murray, 2004;Koga et al, 2010). For example, positive allosteric modulators of GABA A receptors (GABA A R), such as diazepam or allopregnanolone, decreased SCO amplitude and frequency and acted synergistically (Cao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the spinal neural circuits were triggered by disruption of the afferent basal firing, and this effect was mimicked by the application of a group II mGluR antagonist, while the agonists are known to produce alleviating effects on neuropathic pain (Simmons et al, 2002;Jones et al, 2005). Activation of group II mGluRs reduces presynaptic transmitter release (Goudet et al, 2009), hyperpolarizes postsynaptic neurons by opening G-protein-coupled inward rectifier K ϩ channels (Irie et al, 2006;Lee and Sherman, 2009), and modulates spontaneous Ca 2ϩ spikes (Koga et al, 2010). Stimulation of the M/U and R/Mc nerves produced fluorescence increases in the same cortical area (data not shown).…”
Section: Spinal Mechanism Underlying the Initial Phase Of Neuropathicmentioning
confidence: 99%